Improving Student’ English-Speaking Skills Through The English Day Program - Nitya Aryaputri; Nita Kaniadewi (Institut Agama Islam Negeri Palopo, 2024)
Indonesian students often struggle with English-speaking proficiency due to limited practice opportunities and lack of confidence. This study aimed to evaluate the effectiveness of a mandatory English Day program at SMA 90, where students were required to use English exclusively with consequences for non-compliance. A rigorous experimental design, incorporating both pretest and post-test measurements, was used to investigate the English Day program's impact. Seventy students were randomly divided into an experimental group participating in the program and a control group. Utilizing a structured oral test to assess pronunciation, grammar, vocabulary, and fluency, significant enhancements were found in all areas for the experimental group after the program (p < 0.001), with an average improvement of 5.11 points compared to the control group. This study concludes that the mandatory English Day program is effective in enhancing English-speaking proficiency in non-native English-speaking environments. Keywords: English as a Foreign Language (EFL) learners; English Day program, English-speaking proficiency